Social shopping em redes sociais : potencial e vantagens do social shopping em Portugal - Ferreira, Joana Filipa da Silva (2018)
Dissertation presented as the partial requirement for obtaining a Master's degree in Information Management, specialization in Knowledge Management and Business Intelligence